Uji Aktivitas Antibakteri Ekstrak Etanol Biji Mangga (Mangifera indica L.) terhadap Propionibacterium acnes - Zulvia Faridatul Munawaroh (University Of Darussalam Gontor, 2017)
This study aims to utilize mango seed waste and to determine the antibacterial activity of the mango seed. Utilization of mango seeds can be used as an alternative to prevent and treat acne due Propionibcterium acnes.In this study tested the in vitro antibacterial activity against Propionibacterium acnes bacteria. Crude drug percolation mango seed made with ethanol, antibacterial activity of mango seed extract was tested by paper disc diffusion method to determine the value of Minimal Inhibitory concentration (MIC).The ethanol extract mango seed with a concentration of 60% or 0,6g / ml ethanol extract of mango seed has inhibitory zone up to 13.67 mm, at a concentration of 40% or 0,4g / ml extract menghasilkan10,1 mm and at a concentration of 20% or 0,2g / ml extract resulted in inhibition zone diameter of 10.43 mm contained in Kisara 10-20 mm. The ethanol extract mango seed has antibacterial effectiveness against bacteria Propionibacterium acnes that is strong enough. are expected to inhibit the growth of bacteria that causes acne so as to prevent and eliminate acne.